Geodynamics evaluation and geothecnic modelling of Madrigal landslide – Arequipa - Gómez Avalos, Juan Carlos (2017)
The district of Madrigal, Province of Caylloma, Arequipa, is affected by a rotational slip that has been activated since 1959 and which currently shows a high danger and therefore levels of high physical vulnerability. This locality is based on fine foundation soil of lacustrine origin. Studies of photointerpretation of aerial photos of the years 1955, 1970 and 1997 determined that in almost 50 years the landslide of Madrigal increased the unstable area by 0.6 km2. The sliding rotational type that affects the physical safety of Madrigal involves 70% of the area of the district. Geodetic monitoring with GPS and EDM between 2001 and 2014 displacement rates were established between 0.3 and 0.4 m respectively.The stability analysis in the sectors Ushina and Pullhuay yields values of Safety Factor (FS) less than 1 in static and pseudo-static condition and numerical modeling show that the middle and lower part of Madrigal is in critical unstable condition.To reduce vulnerability, a crowning drainage of 500 m is proposed for the height of the 3290 m height, a stabilizing filler at the foot of the main escarpment (dimension 3090 m) and a gabion type support structure in the bottom. In the middle part, there are benches with a drainage system to reduce the hydraulic load.